Systematic revision of the fruit fly genus Carpophthoromyia Austen (Diptera, Tephritidae) - de Meyer, Marc (Zootaxa, 2006)
The Afrotropical fruit fly genus Carpophthoromyia Austen is revised. In total, 17 species are recognized of which 7 are new to science: C. debeckeri sp.n., C. dividua sp.n., C. flavofasciata sp.n., C. interrupta sp.n., C. radulata sp.n., C. schoutedeni sp.n. and C. virgata sp.n.. Carpophthoromyia amoena Enderlein is considered a junior synonym of C. vittata (Fabricius). C. angusticeps Bezzi is considered not to belong to Carpophthoromyia but to the gastrozonine genus Clinotaenia Bezzi: Clinotaenia angusticeps (Bezzi) comb.nov. A lectotype is designated for each of C. litterata, C. pseudotritea, and C. tessmanni. All species are described or re-described, with illustrations of wing patterns and male and female terminalia where deemed necessary for unambiguous identification. An identification key to species is provided.